Role of Computed Tomography in the Evaluation of Different Suprasellar Masses with Histo Pathological Correlation (Bangladesh Journal of Radiology and Imaging, 2026)
Introduction: Computed tomography (CT) plays a pivotal role in assessing suprasellar masses due to its ability to provide detailed anatomical information. This imaging modality aids in delineating the extent, composition, and surrounding structures, crucial for guiding further management and correlating findings with histopathological diagnosis. Objective of this study is to evaluate the effectiveness of computed tomography (CT) in identifying and characterizing various suprasellar masses and to correlate these imaging findings with histopathological results.Methods: This study was carried out in Department of Radiology and Imaging with collaboration of Department of Neurosurgery,BSMMU and DMCH for a period of 1 year. Patients with suprasellar masses who have undergone CT scan before surgery andhistopathological study was carried out post operatively were included in this study irrespective of age and sex. Total 60 patients age ranging between 7 and 55 years (with a mean age of 30.18 years) were included in the study.Results: The mean age of the patients were 30.18 years of whom 56.7 % patients were male and 43.3% were female. Commonest 3 suprasellar masses diagnosed radiologically include pituitary macroadenoma (60%), craniopharyngioma (16.67%) suprasellar and parasellar meniogioma(13.34%).After histopathology 51% pituitary macroadenoma,18% craniopharyngioma and 16% suprasellar parasellar meningioma were confirmed. Conclusion: It was concluded that CT scan can be accepted as a primary imaging modality in the diagnosis of different suprasellar masses. This study was limited to the patients who underwent CT with subsequent histopathological examination. MRI can be added as an additional imaging modality in solvent patients and its diagnostic accuracy can be compared to CT.